2018
DOI: 10.1016/j.ygcen.2018.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone actions on male reproductive system of teleost fish

Abstract: Thyroid hormones (THs) play important roles in the regulation of many biological processes of vertebrates, such as growth, metabolism, morphogenesis and reproduction. An increasing number of studies have been focused on the involvement of THs in the male reproductive system of vertebrates, in particular of fish. Therefore, this mini-review aims to summarize the main findings on THs role in male reproductive system of fish, focusing on sex differentiation, testicular development and spermatogenesis. The existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 59 publications
0
45
0
2
Order By: Relevance
“…In isolated rainbow trout ovarian follicles, T3 treatments enhanced gonadotropin-induced E2 secretion (53). In male fish, thyroid hormones significantly alter spermatogenesis (56). In zebrafish, T3 treatment was shown to stimulate Sertoli cell and spermatogonia type-A proliferation in testis (62).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In isolated rainbow trout ovarian follicles, T3 treatments enhanced gonadotropin-induced E2 secretion (53). In male fish, thyroid hormones significantly alter spermatogenesis (56). In zebrafish, T3 treatment was shown to stimulate Sertoli cell and spermatogonia type-A proliferation in testis (62).…”
Section: Introductionmentioning
confidence: 98%
“…A number of studies have demonstrated actions of thyroid hormone on reproduction in both female and male (52)(53)(54)(55)(56). In murrel, Channa gachua, and a carp, Catla catla, as well as Ranid frogs, GnRH variants increased plasma T4 levels (57,58), although no changes in T3 levels were observed in the goldfish following GnRH treatment (59).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 27,708 unigenes were clustered into 67 GO terms under three different GO categories containing (biological process (BP), cellular component (CC) and molecular function (MF). The number of unigenes in each GO term were shown in Fig 2A. The top 3 terms ranked by number of unigenes in BP were cellular process (17,477), single-organismal process (16,219) and biological regulation (11,558). For CC, unigenes were mainly involved in cell (16,229), cell part (16,151) and membrane (11,815).…”
Section: Go and Kegg Analysis Of C Lucidus Transcriptomesmentioning
confidence: 99%
“…The number of unigenes in each GO term were shown in Fig 2A. The top 3 terms ranked by number of unigenes in BP were cellular process (17,477), single-organismal process (16,219) and biological regulation (11,558). For CC, unigenes were mainly involved in cell (16,229), cell part (16,151) and membrane (11,815). For MF, binding (16,123) was the most prevalent, followed by nucleic acid binding catalytic activity (10,504) and signal transducer activity (1,974).…”
Section: Go and Kegg Analysis Of C Lucidus Transcriptomesmentioning
confidence: 99%
See 1 more Smart Citation